Expanding Demand for Master’s Degree Programs in Interdisciplinary Studies in Education in Mongolia - Oyuntsetseg Namjildorj (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The fourth revolution of industrialization has enormously influenced the education sector and needs to be dynamic and sensible in light of the changeable requirements of employers. Specifically, higher education institutions (HEIs) must focus on the global labor market to offer an innovative curriculum and attract prospective students. One of the current trends in the higher education sector is to design interdisciplinary degree programs. The interdisciplinary master's degree program is relatively new in Mongolian tertiary education. Therefore, we aimed to identify the need for a master’s degree program in interdisciplinary studies in education from the perspective of prospective students and also determine the areas of studies that have been preferred in the field of education. In this study, two online surveys and a focused-group interview were conducted. Three hundred ten educators were involved in the online surveys and focused-group interviews. The research questions were created on Google form, data was collected electronically, and focused group interviews were conducted simultaneously. The findings indicated that 52% of the prospective students preferred a master’s degree program in interdisciplinary studies in education, and a diverse combination of areas has been demanded, in particular, education and modern teaching methodology (26.4%); teaching and linguistics (25.5%); education and international studies (23%) and, teaching and psychology (19.4%). The other important finding was that interdisciplinary studies would be able to provide the necessary knowledge and skills that make graduates competitive in the labor market.